2012
DOI: 10.4104/pcrj.2012.00004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of graphic format on perception of change in biological data: implications for health monitoring in conditions such as asthma

Abstract: Background: Variation in graphic format can substantially influence interpretation of data. Despite a large body of literature on the optimal design of graphs, little attention has been paid to the format of charts for health monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Extant research is unclear whether (18). Prior studies confirmed that graphic elements influence perceived impact and health-related behavioral intentions (87), as well as data interpretation (88). Our sample reiterated existing research, finding that analytical and graphic output features frequently went along with self-monitoring features in the sample (assigned to perceived impact of a diabetes app use).…”
Section: Discussionsupporting
confidence: 83%
“…Extant research is unclear whether (18). Prior studies confirmed that graphic elements influence perceived impact and health-related behavioral intentions (87), as well as data interpretation (88). Our sample reiterated existing research, finding that analytical and graphic output features frequently went along with self-monitoring features in the sample (assigned to perceived impact of a diabetes app use).…”
Section: Discussionsupporting
confidence: 83%
“…Long-term PEF monitoring is largely reserved for patients with more severe asthma, those with impaired perception of airflow limitation, and other specific clinical circumstances. When PEF is used, data should be displayed on a standardised chart with low aspect ratio to avoid misinterpretation [ 32 ].…”
Section: Chapter 2: Assessment Of Asthmamentioning
confidence: 99%
“…• 130 One such chart is available for download from www.woolcock.org.au/moreinfo/. There is increasing interest in internet or phone-based monitoring of asthma.…”
Section: Omentioning
confidence: 99%